2020
DOI: 10.1021/acssynbio.0c00070
|View full text |Cite
|
Sign up to set email alerts
|

Functional Identification of Two Types of Carotene Hydroxylases from the Green Alga Dunaliella bardawil Rich in Lutein

Abstract: The salt-tolerant unicellular alga Dunaliella bardawil FACHB-847 can accumulate large amounts of lutein, but the underlying cause of massive accumulation of lutein is still unknown. In this study, genes encoding two types of carotene hydroxylases, i.e., β-carotene hydroxylase (DbBCH) and cytochrome P450 carotenoid hydroxylase (DbCYP97s; DbCYP97A, DbCYP97B, and DbCYP97C), were cloned from D. bardawil. Their substrate specificities and enzyme activities were tested through functional complementation assays in Es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…Some protists have plastids acquired by tertiary symbiosis of green algae (Keeling, 2010), and they may have obtained CYP97 genes by such symbiosis. Plant CYP97s catalyze ring hydroxylation of a-and b-carotenes and their monohydroxylated derivatives, a function that is conserved from green algae and through land plants (Kim et al, 2009;Liang et al, 2020). Neofunctionalization of a CYP97 for production of the acyclic diterpene plaunotol, known for its anti-gastric-ulcer properties, has been reported for Croton stellatopilosus.…”
Section: Functionalities Of Conserved Cyp Familiesmentioning
confidence: 99%
“…Some protists have plastids acquired by tertiary symbiosis of green algae (Keeling, 2010), and they may have obtained CYP97 genes by such symbiosis. Plant CYP97s catalyze ring hydroxylation of a-and b-carotenes and their monohydroxylated derivatives, a function that is conserved from green algae and through land plants (Kim et al, 2009;Liang et al, 2020). Neofunctionalization of a CYP97 for production of the acyclic diterpene plaunotol, known for its anti-gastric-ulcer properties, has been reported for Croton stellatopilosus.…”
Section: Functionalities Of Conserved Cyp Familiesmentioning
confidence: 99%
“…The peak of zeaxanthin (426, 452, 478 nm) appeared at 10.62 min by HPLC, and the peak area of β-carotene was very low, which indicated that D. salina β-carotene hydroxylase (DsBCH) had high catalytic activity and could fully convert intracellular β-carotene into zeaxanthin (Figure 3c). Our previous study also found that BCH from Dunaliella bardawil could synthesize zeaxanthin from β-carotene via β-cryptoxanthin, and the products of the lycopene-producing E. coli carrying DbLcyB and DbBCH contained more intermediate β-cryptoxanthin with a large amount of β-carotene which had not been completely transformed into β-cryptoxanthin and zeaxanthin (Liang et al, 2020). DsBKT, like other ketoalkylases, also has the ability to keto β-carotene, and its ketoalkylation ability is very strong.…”
Section: Efficient Ketolase Activity Toward Zeaxanthin Of Dsbktmentioning
confidence: 89%
“…α-Carotene is then hydroxylated to lutein by nonheme/di-iron carotene hydroxylase (BCH) and heme-containing cytochrome P450-type carotene hydroxylase (CYP97). BCH and CYP97A have hydroxylation activity towards the β-ring of α-carotene, and CYP97C have a hydroxylation activity towards the ε-ring of α-carotene [30,31]. The LCYb and CYP97 family enzymes are widely distributed in microalgae, whereas LCYe and CYP97C are involved in ε-ring formation and hydroxylation in Chlorophyta [32].…”
Section: α-Carotene and Derivatives Synthesismentioning
confidence: 99%
“…This step is highly diversified in carotenoid biosynthesis. Chlorophyta species have two types of β-carotene hydroxylases, BCH and CYP97A [31,34]. The microphytic red alga C. merolae possesses the crtR gene and lacks the BCH and CYP97 genes [15].…”
Section: β-Carotene and Derivatives Synthesismentioning
confidence: 99%